PENGARUH MODEL PEMBELAJARAN PAPAN MEMORI TEHADAP HASIL BELAJAR PKn SISWA KELAS VIII SMPN 1 BUNGARAYA KECAMATAN BUNGARAYA KABUPATEN SIAK - Handayani, Tri; Gimin, Gimin; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to knowing the influence of the memory board learning model against the learning outcomes of citizenship education grade VIII students of State junior high school 1 Bungaraya Bungaraya sub-district Bungaraya District. The strategy that uses the blackboard as a tool to make it easier for students to be able to quickly remember the terms and technical definitions that the learning model entails is only to write the term and the definition is explained verbally. Because in this learning model students are required to actively remember technical terms and definitions. The formulation of the problem in this study is whether there is an influence of the memory board learning model on the learning outcomes of PKn VIII students at Bungaraya Middle School 1 Bungaraya District, Siak Regency. While the sampling technique used random sampling techniques, namely as many as two classes where students of class VIII.2 as the experimental class were given memory board learning models and class VIII.1 as the control class were students who were given conventional methods. Data collection techniques in this study are using observation, documentation, and tests. Based on the results of the study it can be concluded that an increase in student learning outcomes after the memory board model is carried out with the average experimental class (VIII.2) of 77.27% with a variance of 80.47. The average learning outcomes of the control class students (VIII.1) amounted to 64.52% with variance 134, 76. Then this study proved that there was an effect of learning memory board models on the learning outcomes of PKn VIII students at Bungaraya 1ND SMP Bungaraya District, Siak Regency.Â Key Words: Memory Board, Learning Outcomes